Application of Balankin fractal fracture model to the fractal volcanic activity model - Delgado-Granados, Hugo (2015)
This paper shows a series of self-critical reflections of the reality of Latin American volcanology, from an analysis of its strengths, weaknesses, opportunities, and threats (SWOT) held in February 2008 in Antigua, Guatemala. Before the analysis, an account of the efforts made to unite the Latin American volcanological community is presented, up to the formation of an association (the Latin American Association of Volcanology, ALVO according to its Spanish acronym) that will strengthen and promote partnerships between Latin American volcanologists and their institutions for the benefit of society, particularly during eruptive crisis of the numerous active volcanoes in the Latin American region